Religiusitas sebagai Homologizer Moderasi dalam Hubungan antara Dimensi Fraud Diamond dan Kecurangan Akademik pada Perkuliahan Daring (Studi Kasus Mahasiswa Akuntansi) - Tiswiyanti, Wiwik; Herawaty, Netty (Ekonomis: Journal of Economics and Business, 2024)
Acts of dishonesty are often committed by students, especially in online lectures, in order to get a high grade point average (IP). The achievement index is an indicator of success during education and to provide wider job opportunities. Education is all learning experiences that take place and affect the joints of life and affect one's behaviour in life. Accounting students are future accountants, accountants must comply with the accountant's code of ethics and avoid cheating. Academic fraud committed by accounting students is a behaviour that, if often carried out, has an impact on cheating to commit dishonesty in the world of work. The study aims to analyse the direct and indirect effects of the dimensions of the fraud diamond consisting of opportunity, opportunity, rationalisation and ability on academic fraud where religiosity as a moderating variable on the indirect relationship between the dimensions of the fraud diamond and academic fraud. The research population was accounting students in the class of 2019 and 2020 and still active in 2023, totalling 317 at a State University in Jambi City. Sample selection using proposive sampling and obtained a sample of 287. Data analysis using PLS. The results found that the dimensions of the fraud diamond: directly affect academic fraud in online lectures, and indirectly religiosity is not able to provide a strong influence on the relationship between the dimensions of the fraud diamond and academic fraud in online lectures. The research novelty is religiosity as a moderating homologizer, seen from religiosity does not interact or is unable to influence the relationship between the dimensions of the fraud diamond variable and the academic fraud variable in online lectures.